The role of effector proteins on suppression of the plant immune system : a case study: ‘HaRxL21’ - Kumari, Priyanka; Justus Liebig University Giessen (My University, 2022)
Plant diseases result from the interaction between the pathogen and the host plant, where pathogens deploy effector proteins to invade the host immune system to aid colonization. The oomycete Hyaloperonospora arabidopsidis (Hpa) is the causal agent of downy mildew of Arabidopsis thaliana. The oomycete effectors have a conserved ‘RxLR’ motif, which is required for their translocation into the host cell. Here we characterised ‘HaRxL21’, which is an EAR motif-containing Hpa effector that can suppress plant immunity. HaRxL21 expressing lines show enhanced susceptibility against Hpa and Botrytis cinerea. The interaction targets of HaRxL21 were identified, and we confirmed that HaRxL21 interacts with the Arabidopsis transcriptional co-repressor TPL. We have established that HaRxL21 and TPL interact via an EAR motif at the C-terminus of the effector. We show that the EAR motif is required for the interaction with TPL and is necessary for the virulence function of the effector. RNA-seq analysis has revealed the effects of HaRxL21 on host transcription, mainly through the down-regulation of defense-related genes. Hence, this effector mimics the host plant mechanism of EAR motif mediated repression by recruiting TPL to the transcriptional repression site. Moreover, we have provided evidence that HaRxL21 uses the interaction with TPL, and its close relative TPR1, in order to manipulate the plant immunity and enhance susceptibility to both a biotrophic and a necrotrophic pathogen.
Keywords: ddc:500; ddc:570; ddc:600; ddc:630